Versatility of Fear-Potentiated Startle Paradigms for Assessing Human Conditioned Fear Extinction and Return of Fear - Norrholm, Seth D.; Anderson, Kemp M.; Olin, Ilana W.; Jovanovic, Tanja; Kwon, Cliffe; Warren, Victor T.; McCarthy, Alexander; Bosshardt, Lauren; Sabree, Justin; Duncan, Erica J.; Rothbaum, Barbara O.; Bradley, Bekh (Frontiers in Behavioral Neuroscience, 2011)
Fear conditioning methodologies have often been employed as testable models for assessing learned fear responses in individuals with anxiety disorders such as post-traumatic stress disorder (PTSD) and specific phobia. One frequently used paradigm is measurement of the acoustic startle reflex under conditions that mimic anxiogenic and fear-related conditions. For example, fear-potentiated startle is the relative increase in the frequency or magnitude of the acoustic startle reflex in the presence of a previously neutral cue (e.g., colored shape; termed the conditioned stimulus or CS+) that has been repeatedly paired with an aversive unconditioned stimulus (e.g., airblast to the larynx). Our group has recently used fear-potentiated startle paradigms to demonstrate impaired fear extinction in civilian and combat populations with PTSD. In the current study, we examined the use of either auditory or visual CSs in a fear extinction protocol that we have validated and applied to human clinical conditions. This represents an important translational bridge in that numerous animal studies of fear extinction, upon which much of the human work is based, have employed the use of auditory CSs as opposed to visual CSs. Participants in both the auditory and visual groups displayed robust fear-potentiated startle to the CS+, clear discrimination between the reinforced CS+ and non-reinforced CS−, significant extinction to the previously reinforced CS+, and marked spontaneous recovery. We discuss the current results as they relate to future investigations of PTSD-related impairments in fear processing in populations with diverse medical and psychiatric histories.